Functionalized cellulose microfibers as reductant agent to gold nanoparticles and its application on SERRS for sensitive detection of phthalocyanine dye - Dognani, Guilherme [UNESP]; Gomes, Andressa Silva [UNESP]; de Oliveira Setti, Grazielle [UNESP]; Martin, Cibely Silva [UNESP]; Rubira, Rafael Jesus Gonçalves [UNESP]; Constantino, Carlos José Leopoldo [UNESP] (Elsevier, 2023)
Cellulose-based materials have drawn great attention in the world due to its abundance, renewable source, biodegradability, and easy functionalization of structure. Herein, microfibrillar cationic dialdehyde cellulose (CMF) using Girard's reagent T was produced. The functional groups of CMF were employed to reduce gold(III) into nanoparticles (AuNPs) which remain anchored on the fibers, designing a never-before encountered hybrid CMF/AuNPs. The AuNPs are well-dispersed, presenting an average size of 25 nm. The CMF showed an excellent reducing agent without any other chemicals, providing a green synthesis route. The novel hybrid was applied as substrate for surface-enhanced resonance Raman scattering (SERRS) spectroscopy to nickel(II) tetrasulfonated phthalocyanine (NiTsPc) detection as a proof-of-principle. A detection limit (LOD) in order of 10-7 mol/L and a quantification limit (LOQ) of 3.58 × 10-7 mol/L for the band at 1359 cm-1 were found. The CMF/AuNPs held considerable promise as an effective SERRS substrate for sensitive detection and quantification of trace molecules.